INVESTIGATING THE IMPACT OF MYRTLE PLANT LEAF EXTRACT (MYRTUS COMMUNIS (L.)) ON THE ADULT RUSTY FLOUR BEETLE TRIBOLIUM CASTANEUM, (HER BEST) AN INTERMEDIATE HOST OF THE DWARF TAPEWORM HYMENOLEPIS NANA (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This study was conducted for the prevention and reduction of the risk of infection with dwarf tapeworm disease caused by Hymenolepis nana Using an extract from the leaves of Myrtus communis (L.) plant at concentrations of 10%, 15%, 20%, and 25%, the effect was tested for four treatments were used, with each treatment having five replicates for durations of 1 hour, 2 hours, 6 hours, 12 hours, and 24 hours، againstthe adults of Tribolium Castaneum (Herbest) from the family Tenebronidae and the order Coleoptera which is considered an intermediate host for this tapeworm The results showed the highest mortality rate for red flour beetle adults was 72% and 84% for concentrations of 20% and 25%, respectively, after 24 hours of exposure. The lowest mortality rate was 8% for concentrations of 10% and 15% after only 1 hour of exposure There were no significant differences between the time replicates when exposed to concentrations of 10% and 15%. However, there were significant differences between the replicates for the treatments with concentrations of 20% and 25%, at a significance level of p ≤ 0.05. Exposure to concentrations of Myrtus communis (L.) leaf extract leads to the death of the red flour beetle Tribolium castaneum (Herbst), which reduces the size of infection with the dwarf tapeworm Hymenolepis nana by decreasing the number of T. castaneum larvae that serve as intermediate hosts for the tapeworm.